CFD simulations to study bed characteristics in gas–Solid fluidized beds with binary mixtures of Geldart-B particles: A qualitative analysis - Ganguli, Arijit; Bhatt, Viraj (Frontiers in Energy Research, 2023)
Bed characteristics of fluidized beds in binary mixtures in Geldart-B particles have been investigated using CFD simulations. An effort has been made to study the phenomena of segregation and mixing using simulations both qualitatively and quantitatively at a range of superficial gas velocities (0.3 m/s – 0.6 m/s) and two different bed heights. The study has been divided into two parts. In Part-I the present part of the study), a qualitative analysis of flow patterns for 7 different binary mixtures has been presented. The quantitative analysis (including particle and gas velocity profiles, particle volume fraction profiles and correlations for minimum fluidization velocity and pressure drop) will be presented in Part-II of the two parted work. First, the CFD model is validated using experimental data from the literature. Qualitative predictions of volume fraction profiles of small-sized particles show that for mixtures range 40% to 60% large particles of Geldart-B type, the bubble and solid particle dynamics are different from that of single particles, for the superficial gas velocities presently considered. In contrast to the single particles in the given superficial gas velocity range are in bubbling regime, the binary particles show a transition from bubbling to slugging to turbulent regime as per qualitative analysis. Homogeneous regime is observed for lower superficial gas velocities for mixtures consisting 0 to 20% large particles.